Thermoplastics composites vs. thermoset composites - Mokhtar, Munirah (Faculty of Chemical & Natural Resources Engineering, 1995)
The possibility of property enhancement through fiber reinforcement is among the key factors that make plastics an attractive candidate for new engineering materials. Both thermoplastics and thermosets can gain the benefit of fiber reinforcement whereby various system has been developed to offer flexibility of choice to designers and manufacturers . The aim of this paper is therefore to briefly review the advantages and the limitations of thermoplastics and thermosets composites in terms of material properties and processing characteristic.